Galactose Oxidase Enables Modular Assembly of Conjugates from Native Antibodies with High Drug‐to‐Antibody Ratios. Issue 9 (20th January 2022) - Angelastro, Antonio; Barkhanskiy, Alexey; Mattey, Ashley P.; Pallister, Edward G.; Spiess, Reynard; Goundry, William; Barran, Perdita; Flitsch, Sabine L.
Abstract: The potential of antibody conjugates with high drug loading in anticancer therapy has recently been highlighted by the approval of Trastuzumab deruxtecan and Sacituzumab govitecan. These biopharmaceutical approaches have spurred interest in bioconjugation strategies with high and defined degrees of drug‐to‐antibody ratio (DAR), in particular on native antibodies. Here, a glycoengineering methodology was developed to generate antibody drug conjugates with DAR of up to eight, by combining highly selective enzymatic galactosylation and oxidation with biorthogonal tandem Knoevenagel–Michael addition chemistry. This four‐step approach offers a selective route to conjugates from native antibodies with high drug loading, and thus illustrates how biocatalysis can be used for the generation of biopharmaceuticals using mild reaction conditions. Abstract : Glycoengineering : The synthesis of antibody–drug conjugates with high drug loading from native antibodies is of great interest for development of biopharmaceuticals. Here, selective biocatalysis using galactose oxidase and tandem Knoevenagel–Michael addition conjugation chemistry are combined to achieve molecular drug‐to‐antibody ratios of up to eight.